(untitled) (International Journal of Engineering and Computer Science, 2017)
Energy consumption is a significant issue in ad hoc networks since mobile nodes are battery powered. In order to prolong the lifetime of ad hoc networks, it is the most critical issue to optimize the energy consumption of nodes. In this paper, we propose a power aware routing protocol for choosing energy efficient optimum route selection & network approach. This system also considers transmission power of nodes and residual energy as energy metrics in order to maximize the network lifetime and to reduce energy consumption of mobile nodes. The objective of our proposed system is to find an optimal route based on two energy metrics while choosing a route to transfer data packets. This system is implemented by using NS-2.35. Simulation results show that the proposed routing protocol E-EPAR with transmission power and residual energy control mode can extend the life-span of network and can achieve higher performance when compared to EPAR and DSR routing protocols.